Diversity and function of tumor-associated macrophages in brain metastases: mechanisms and therapeutic prospects - Ma, Yingping; Wang, Hongyu; Dou, Xinman; Li, Qiang (Frontiers in Immunology, 2026)
Brain metastasis significantly worsens prognosis in late-stage cancer., with Its treatment hindered by the blood-brain barrier (BBB) and an immunosuppressive tumor microenvironment. Within this environment, tumor-associated macrophages (TAMs) represent the predominant immune population. Through their roles in immune modulation, angiogenesis, and tumor invasion, TAMs are critical drivers of disease progression. TAMs are highly heterogeneous. While traditionally categorized into M1 (anti-tumor) or M2 (pro-tumor) phenotypes, this dichotomy is an oversimplification. Recent single-cell studies have revealed a spectrum of functional subpopulations, such as lipid-associated, interferon-responsive, and pro-angiogenic TAMs, with M2-like states typically prevailing to mediate immunosuppression. This review explores the diversity and functions of TAMs in brain metastasis. We first detail their biological characteristics, including origins, heterogeneous subtype classifications (e.g., lipid-associated macrophages that extend beyond the simple M1/M2 dichotomy), and polarization states. We further discuss how polarization is regulated by signaling pathways (e.g., STAT, NF-κB) and microenvironmental factors (e.g., hypoxia, metabolic reprogramming). We examine TAM roles from pre-metastatic niche formation to tumor colonization, using breast and lung cancer brain metastases to illustrate how TAMs disrupt the BBB and facilitate immune evasion through molecules like ANGPTL4 (angiopoietin-like 4) and MMP9. Key pathways of TAM-tumor cell interactions, including neuro-cancer interactions, immune-metabolic regulation, and exosome-mediated communication, are also discussed. Targeting TAMs offers promising therapeutic avenues. These strategies include reprogramming TAMs (e.g., using CSF1R inhibitors), combining TAM-targeted therapy with immune checkpoint inhibitors, and developing novel approaches such as nanotechnology and CAR-macrophages. However, several challenges remain, including TAM heterogeneity, lack of targeting specificity, and the obstacle of BBB delivery. Future research should leverage technologies like single-cell sequencing and spatial transcriptomics to decode TAM heterogeneity, and develop personalized treatments based on biomarkers such as GPNMB and TRAIL, aiming to improve patient outcomes in brain metastasis.